12 A qualitative study of factors that helped prepare athletes for Special Olympics sport programs. (29th October 2021) - Gander, Sarah; McNally, Jillian; Flood, Kate; Hanson, Natasha
Abstract: Primary Subject area: Developmental Paediatrics Background: Special Olympics (SO) is working to introduce more child and youth programs provincially and improve currently available programs. To date, there is little research published surrounding the experiences of SO athletes. Given the aim of SO to improve and grow the experience and health of youth, the present study explores the experiences of SO athletes and caregivers to understand what prepares athletes for SO programs and competition. Objectives: 1. To describe the experience of SO athletes and caregivers and understand what best prepared them for their involvement in organized sport and physical activity. 2. To offer evidence-based strategies for creating an inclusive and encouraging environment for sports and physical activity for healthy active living and/or preparation for SO involvement. Design/Methods: Both athletes and caregivers participated in semi-structured, conversation-based interviews. Eight English-speaking athletes involved in a variety of sports from around the province were interviewed, and four of these interviews included caregivers. Interviews were transcribed and coded using thematic analysis. Results: Five themes were identified throughout these interviews. The importance of a supportive environment emerged as a strong theme. Athletes valued the support of caregivers, coaches, and other players and felt this helped them improve and garner more enjoyment from their sport. Many athletes and caregivers discussed what motivated them to get involved and stay involved in SO. Common motivators included: a healthy, active lifestyle, friendships, and social skills. Barriers to involvement also were commonly discussed and included parental support, transportation, dissemination of information, and health concerns. Additionally, many athletes and caregivers felt that early involvement, starting with the basics, was important for developing skills to help transition to sports and competition. Finally, types of programming, including non-specialized vs. specialized activities, were discussed. Advantages of non-specialized activities included more time for practice and integration into society. Conclusion: It is important that programs create a supportive environment, as this helps athletes improve and leads to further enjoyment. There is benefit to participation in non-specialized activities. Future programs could consider the addition of inclusive activities, or promotion of these activities. The motivators for involvement should be encouraged, including friendships/social skills and a healthy/active lifestyle. The barriers identified should be addressed when developing programming. Early involvement and learning basic motor skills play an important role in preparing athletes for sports, and competition and may lead to further involvement in sports. Early participation should be encouraged, and programs should find ways to reach more of this population, possibly through schools or physicians.